The Effect of Profitability Ratios on Financial Distress in Islamic Commercial Banks in Indonesia - hasanah siregar; darwis harahap; abdul nasser hasibuan; nofinawati nofinawati (Institut Agama Islam Negeri Padangsidimpuan, 2020)
The background of this research is based on the existing theory that the higher the level of profit sharing, the Musyarakah financing will increase, conversely if the profit sharing rate decreases, the Musyarakah financing will tend to decrease. This is not in accordance with the financial statements of sharia commercial banks and sharia business units for the 2016-2018 period. So that the formulation of the problem in this research is whether there is an effect on the level of revenue sharing towards the financing of Musyarakah in Sharia Commercial Banks and Sharia Business Units for the 2016-2018 Period. And this study aims to determine whether there is an effect of the level of profit sharing on the financing of Musyarakah in Sharia Commercial Banks and Sharia Business Units for the 2016-2018 Period. This study deals with financial statements that discuss the notion of financing, elements of financing, financing functions, financing benefits, understanding Musyarakah, types of Musyarakah, Al-Musyarakah benefits, Understanding of results, basic principles of the concept of revenue sharing, method of calculation of results , the application of profit sharing in Islamic banking, in connection with the approach taken is the theories relating to the financing of Musharaka, profit sharing. This type of research is descriptive quantitative research. The data source used is secondary data taken through www.ojk.go.id. Data collection techniques used are literature study and documentation based on financial reports on the level of profit sharing, musyarakah financing at Sharia Commercial Banks and Sharia Business Units for the 2016-2018 Period. The data analysis technique used is descriptive analysis test, normality test, simple linear regression analysis test, hypothesis test: t test, determination coefficient test (R2). The results of the study partially indicate that the level of revenue sharing affects the financing of Musyarakah.